A Case of Covaxin-Induced Focal Sclerosing Glomerulonephritis (Collapsing Variety) - Mahajan, Mohit; Goswami, Shraddha; Pahwa, Naresh; Malviya, Vijay; Shukla, Vishnu; Chhabra, Trishla (BOHR International Journal of General and Internal Medicine, 2022)
We report on the development of focal glomerular segmental sclerosis FSGS (collapsing variety) with nephritic symptoms immediately after receiving the first injection of the Covaxin COVID-19 vaccination and acute kidney damage (AKI) (Bharat-Biotech). A 45-year-old lady who had previously been healthy was taken to a hospital outside of the city after developing a headache and pedal edoema. She had gotten the first shot of the immunisation 10 days ago. She experienced bilateral lower limb edoema 4 days following the injection, which turned into anasarca over time. At her admission, UPCR was 7.2 and serum creatinine was 0.9 mg/dl. Over the following days, kidney function continued to deteriorate, and serum creatinine rose to 3.2 mg/dl. The patient was sent to our institution for a kidney biopsy after an abdominal ultrasound revealed normal-sized bilateral kidneys. After doing a kidney biopsy, the results were consistent with FSGS. MCD, IgA nephropathy, and anti-GBM are only a few examples of the diverse glomerulonephritis. Several m-RNA vaccinations have been associated with nephritis in the past, but not the Covaxin COVID-19 vaccine. At this point, the correlation between the immunisation and FSGS is temporal, by exclusion, and in no way clearly established. To assess the actual prevalence of this potential vaccination adverse effect, we must wait for more reports of instances that are comparable to those already reported.